Botschafter Europas Richard Nikolaus Coudenhove-Kalergi und die Paneuropa-Bewegung in den zwanziger und dreißiger Jahren - Ziegerhofer-Prettenthaler, Anita (Böhlau, 2004)
In 1923 Count Richard Coudenhove-Kalergi, offspring of an aristocratic family in the Austro-Hungarian Monarchy, published the book Paneuropa which was soon translated into almost all important languages of the world. A movement was launched under the same name and soon became the synonym for all efforts concerning the creation of a united Europe in the interwar period and even beyond. The Count was convinced of the necessity to create Paneurope the main reasons being the danger of a second world war, Bolshevist Russia and the economic power of the United States of America. Since 1925 Paneurope Unions were founded in nearly every European capital; the headquarter were Vienna (Hofburg). But the movement failed in mobilizing the masses. Coudenhove who was the embodiment of Paneurope was only in contact with statesmen, industrial leaders and intellectuals. His great merit was the confrontation of European governments with the idea of a united Europe, the rising of European question. Despite of all his efforts European politicians were not able to realize the importance of "United States of Europe" in those days. Nationalism was too strong and there seemed to be no willingness to give up parts of the own sovereignity and to develop a better understanding for democracy.The study presents a comprehensive view of the Paneuropean Movement during the interwar period including records of the Moskow Archive (captured material). It opens with a biographical sketch followed by the political program and how it was adapted to the political situation of those days; other main items are fund raising, financial organisation and propaganda. Also, there is an analysis of Paneurope in interaction with contemporary Austrian and European policies. Another chapter is dedicated to the ideas to unite Europe economically (since 1933) or on a cultural basis (saving the Abendland). The longitudinal views are completed by sectional views which focussed on the way how Coudenhove and his Paneurope Movement dealt with ideologies and mental streams of these days; They fought Bolshevism and since 1933 against National Socialism; they sympathized with Italian Fascism; Paneurope was anti-democratic and aristocratic.Some of the aims were revolutionary but many people regarded them as utopian. In comparison with the European Union there are certain parallels between European Union and Paneurope. Today we can see Paneurope - with restrictions - as an avant-garde of the European Union.